ANALISIS PENGGUNAAN APLIKASI PENDAFTARAN ONLINE DENGAN MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Firdaus, Muhammad; Syahada, Jihan; Handoko, Bobi; Marzuki, Asep (LPPM Universitas Awal Bros, 2023)
MIRAI is an online registration application launched by Arifin Achmad Hospital, Riau Province. To find out the extent to which the utilization and views of the public regarding the MIRAI online registration application, it is necessary to test the technology acceptance model. The technology acceptance model is a theory that explains the state of technology users accepting and using technology. The variables used by the researcher are the perception of the ease of using technology and the perception of the usefulness of technology to determine a person's behavior in using technology. The general objective of this study is to determine the effect of the technology acceptance model on online registration at the Arifin Achmad Hospital, Riau Province.This research used a quantitative descriptive research design with purposive sampling method according to the researcher's criteria and a sample of 99 users of the MIRAI online registration application. This research was conducted on June 22 – July 29, 2022 at the heart disease polyclinic and internal medicine polyclinic at the Arifin Achmad Hospital, Riau Province.The results showed that the perception of convenience can affect a person's attitude towards the use of the MIRAI online registration application through a linearity test of 0.094. And the perception of usefulness can affect a person's attitude towards the use of the MIRAI online registration application through a linearity test of 0.086, so that both hypotheses are significant because the value > 0.05 obtained from data processing through the SPSS 26.0 application.The conclusion of this research is the implementation of the TAM acceptance model that has been made has obtained the factors that affect user acceptance of the use of MIRAI and the variables there is an influence. The suggestion from this research should then be able to develop a TAM research model using more variables.